Pengaruh Perputaran Kas dan Perputaran Persedian terhadap Profitabilitas Perusahaan Manufaktur yang Terdaftar di BEI - Nasution, Nur Halisa; Siska, Elmira; Indra, Natal (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This study aims to analyze the effect of cash turnover and inventory turnover on the level of profitability of food and beverage manufacturing companies listed on the IDX in 2019-2022. This research method uses a quantitative approach using company financial data during the specified research period. With the purposive sampling technique, the number of samples in this study was obtained as many as 31 companies. Data analysis techniques include descriptive statistical tests, classical assumption tests, multiple regression tests, hypothesis tests consisting of partial tests (t test) and simultaneous tests (F test), test the coefficient of determination. The data were processed using the SPSS version 22 program. The results showed that partially, cash turnover (CTR) had a positive and significant effect on company profitability. Then, inventory turnover (ITO) has a positive and significant effect on company profitability. Furthermore, simultaneously, both CTR and ITO have had a positive and significant effect on the profitability of food and beverage manufacturing companies listed on the IDX in 2019-2022. The practical implication of this research is that company management can use the findings of this research to optimize the management of their cash flow and inventory turnover, so as to increase the company's profitability.